Kinetic effects in the local plasma resonance region excited by modulated electron beam: 2D simulation - Anisimov, I.O.; Velykanets', D.M.; Litoshenko, T.Eu. (Вопросы атомной науки и техники, 2008)
Electrons' and ions acceleration in the local plasma resonance region (LPRR) excited by thin modulated electron beam was studied via computer simulation using PIC method. The region of electrons' and ions' acceleration was found out. At the late stage of the process the HF field excited in the LPRR perturbs the initial plasma density distribution. In that time the accelerated electrons velocity is directed at some angle to the plasma density gradient. Ions acceleration on the late stages of interaction is caused by ambipolar field. За допомогою комп’ютерного моделювання досліджується прискорення електронів та іонів плазми в області локального плазмового резонансу (ОЛПР), збуджуваній модульованим електронним пучком. Досліджуються області прискорення електронів та іонів плазми. На пізніх стадіях взаємодії високочастотне поле, що збуджується в ОЛПР, деформує профіль концентрації плазми, і електрони прискорюються під деяким кутом до напряму градієнту концентрації плазми. Прискорення іонів на пізніх часах взаємодії відбувається під дією амбіполярного поля. При помощи компьютерного моделирования исследуются ускорение электронов и ионов плазмы в области локального плазменного резонанса (ОЛПР), стимулированной модулированным электронным пучком. Исследуются области ускорения электронов и ионов плазмы. На поздних стадиях взаимодействия высокочастотное поле, возбуждаемое в ОЛПР, деформирует профиль концентрации плазмы, и электроны ускоряются под некоторым углом к направлению градиента концентрации плазмы. Ускорение ионов на поздних этапах взаимодействия происходит под воздействием амбиполярного поля.